Interpretation Research: A New Impetus? - Gile, Daniel (HERMES - Journal of Language and Communication in Business, 2017)
Attitudinal changes are a salient recent development in the interpreting research community. They include an aspiration to science and to interdisciplinarity. However, such an aspiration is difficult to implement because of training- and motivation-related constraints, as well as difficulties in access to field data. The most promising avenues for development lie in research promotion policies in interpretation schools, and in the involvement of non-interpreting researchers in interpretation research.